The relationship of free fatty acids with the binding of oestradiol to SHBG and to albumin in women. - Key, T; Pike, M; Moore, J; Wang, D; Morgan, B (1990)
Free fatty acid concentration, sex hormone binding globulin (SHBG) concentration, % free oestradiol and % SHBG-bound oestradiol were measured in fasting and non-fasting serum samples from 48 women. Free fatty acids were 128% higher (P less than 0.001) and % SHBG-bound oestradiol was 11% lower (P = 0.001) in fasting than non-fasting samples, but these changes were not significantly correlated (r = -0.16, P = 0.287). Mean SHBG concentration and % free oestradiol did not differ significantly between fasting and non-fasting samples. Between subject correlations were calculated for measurements from 30 premenopausal women: % free oestradiol was inversely correlated with SHBG and free fatty acids and positively correlated with Quetelet's Index; % SHBG-bound oestradiol was positively correlated with SHBG but was not consistently or significantly related to free fatty acids or Quetelet's Index. It was concluded that physiological increases in free fatty acid concentrations do not increase % free oestradiol and that free fatty acids are less important than SHBG concentration and perhaps other variables in determining differences between individuals in oestradiol binding to SHBG.